Effect of Mineralization of Plant and Animal Residues on Aggregate Stability - Fattah, Omer Ali; Kassim, Jabbar Kathem; Karim, Kamal Hama (Sulaimani Journal for Pure and Applied Sciences, 2018)
The study aims to elucidate the impact of different organic inputs (plants straws and animal residues) on the rate of biodegradation and stability of aggregates in a silty loam soil. A laboratory experiment was performed by using four levels (0, 1, 2, and 100%) of three types of plants straws (wheat, corn and legume) and three types of animal manure (cow, sheep, and poultry) which is incubated at 28ᴼ C for different periods of times (7,14, 21, 28, 42, 56. 70,84,and 112) days. The experiment was setup in completely randomize design with three replicates for each addition level. The results indicated that the mineralized carbon increased gradually with increasing residual percentage and incubation period. The amount of mineralized carbon is increased with the incubation time, but it was obvious in the first 56 days of incubation. The highest degradation percent was observed at lower C: N ratio epically with poultry and legumes. The accumulative mineralized carbon increased with increasing the amount of residual added. Addition of organic substrates significantly improved soil organic C contents, but the type and source of inputs had different impacts. In addition, higher macro- aggregates in the crop residue- and farmyard manure-treated soils resulted in a higher aggregate mean weight diameter (MWD), which also had higher soil organic C contents. The order of MWD values were wheat < corn < legume < cow < sheep < poultry. The value increased in MWD by 154 and 291% in raised level of poultry manure from zero to 1 and 2% respectively.
Keywords: Plant straw; Animal Manure; Aggregate stability; Mineralized carbon; Mean weight diameter